Case Report: Early diagnosis of LAD-III in newborn with persistent leukocytosis and hemangioma-like lesion of the urinary bladder - Pagani, Riccardo; Lorioli, Laura; Favini, Francesca; Severi, Eleonora; Salvi, Marco; Pezzani, Lidia; Iascone, Maria; Migliazza, Lucia; Pellegrinelli, Claudia; Cheli, Maurizio; Provenzi, Massimo; Mangili, Giovanna (Frontiers in Pediatrics, 2025)
Leukocyte Adhesion Defects (LADs) are a group of rare autosomal recessive immune disorders characterized by constitutional defects in the process of leukocyte migration. Among these, LAD-III is the rarest, with only a few cases documented in scientific literature. It is caused by mutations in the FERMT3 gene, impairing integrin function in both white blood cells and platelets. Thus, patients exhibit a variable degree of immunodeficiency along with a severe bleeding tendency referred to as “Glanzmann-like”, due to dysfunctional platelet GPIIb/IIIa. The diagnosis of LAD-III is typically made in infancy or early childhood, following medical evaluations for recurrent infections and bleeding episodes. Here we report the case of a female newborn admitted to our NICU at day four of life with a history of petechial rash and gross hematuria. Radiological and endoscopic assessments revealed a hemangioma-like lesion of the bladder wall. Blood exams showed persistent leukocytosis without signs of infection, associated with mild thrombocytopenia and normocytic anemia. Notably, platelet function assays demonstrated defective aggregation with all agonists tested. Next generation sequencing analysis identified a homozygous nonsense mutation in the FERMT3 gene, ensuring early access to hematopoietic stem cell transplantation, which is the only curative treatment. To the best of our knowledge, this is the first reported case of LAD-III diagnosed in the neonatal period and the first to associate this rare disorder with bladder angiomatosis. This case highlights the importance of early genetic evaluations in newborns with unexplained hematological abnormalities and bleeding tendencies.